Chronic Infection and Venous Thromboembolic Disease - Epaulard, Olivier; Foote, Alison; Bosson, Jean-Luc (Seminars in Thrombosis and Hemostasis, 2015)
Venous thromboembolic disease often arises as a complication of another pathological condition and/or triggering event. Infectious diseases result from both the direct action of the pathogens themselves and their effect on the immune system. The resulting inflammatory process and the coagulation and fibrinolysis processes share common pathways, explaining why infection is associated with thrombosis. In this brief overview, besides certain chronic infectious diseases, we also consider some acute infections, as the mechanisms are likely to be similar, particularly in the initial infective stage or the more acute episodes of a chronic infection. The infectious agent can be viral, bacterial, fungal, or parasitic. However, the literature on the link between infections and venous thromboembolism (VTE) is uneven, favoring infections that are found in more developed countries where physicians have access to VTE diagnostic tools. Thus, large epidemiological studies in this field are restricted to a limited number of the common chronic infectious diseases such as tuberculosis, while for other infections, particularly parasitic and fungal infections, the link with VTE is only evoked in a few scattered case reports.
Keywords: chronic infection; venous thromboembolic disease; VTE